Inequality and attitudes: postcommunism, western capitalism and beyond - Jan Delhey (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1999)
This paper* deals with attitudes towards inequality in cross-national perspective using survey data of the International Social Survey Programme (ISSP) of 1992. Factor analysis shows that perceptions and evaluations of inequality and stratification refer to four attitudinal dimensions: Egalitarianism, meritocratic beliefs, functionalist convictions and the perception of non-universalistic status ascription. With these dimensions one gets an impression of the patterns of attitudes held in different countries. The main differences between post-communist and western capitalist countries concern egalitarian attitudes: East Europeans are much more egalitarian. This applies especially to the role of the state. Concerning the other three dimensions, other variables explain international variation in attitudes better than the belonging to the East or the West. Nevertheless, over the whole range of questions there is a visible separation between post-communist and western capitalist countries - but not into two ,,blocs“, but into a number of ,,families of nations“. Cluster analysis brings together societies that are similar in terms of social history as well as in terms of geography and welfare institutions.
Keywords: 300; Verteilungsgerechtigkeit; Soziale Werte; Osteuropa; Westliche Staaten